Seasonal dynamics of zooplankton in the southern Chukchi Sea revealed from acoustic backscattering strength. (1st February 2017) - Kitamura, Minoru; Amakasu, Kazuo; Kikuchi, Takashi; Nishino, Shigeto
Abstract: To understand the seasonal dynamics of zooplankton in the southern Chukchi Sea, we use observations from a moored multi-frequency echo-sounder from July 2012 to July 2014. Zooplankton biomass, as indicated by area backscattering strength, was high during autumn and low in early spring; the seasonal peak in zooplankton biomass did not coincide with the spring phytoplankton bloom. This suggests that the seasonal zooplankton dynamics in the southern Chukchi Sea are less influenced by local growth of zooplankton during the spring phytoplankton bloom and more influenced by advection of zooplankton from the Bering Sea. The differences between volume backscattering strengths at 200 and 125 kHz suggest that the main acoustic scatterers are large zooplankton (euphausiids and Neocalanus cristatus ) in late summer and autumn and small zooplankton (other copepods) in other seasons. The decrease in acoustic backscatter from large zooplankton from winter to early summer also suggests the unsuccessful overwintering of advected Pacific zooplankton. The temporal mismatch between zooplankton and phytoplankton production suggests that there is still tight pelagic–benthic coupling in the southern Chukchi Sea. Highlights: We observed changes in zooplankton acoustically in the southern Chukchi Sea. Backscattering strength varied seasonally. Large zooplankton dominated mid-summer to autumn; small copepods in other seasons. Peak zooplankton biomass did not coincide with the spring phytoplankton bloom. Most spring-bloom production was not grazed, but likely sank to the sea bottom.